學生知覺教師期望、能力信念、實用價值與內在價值對臺灣八年級學生數理成就之影響：以TIMSS 2011 多層次結構方程式模型為例 Effects of Perception of Teachers' Expectations, Ability Beliefs, Utility Values, and Intrinsic Values on Math and Science Achievement Among Eighth-Grade Students in Taiwan: A Multilevel Structural Equation Model Using TIMSS 2011 - 陳敏瑜 Min-Yu Chen; 游錦雲 Ching-Yun Yu (National Taiwan Normal University, 2017)
本研究以期望價值理論為架構，進行國際數學與科學成就趨勢調查（TIMSS）2011 年臺灣八年級學生數學和科學成就之多層次結構方程式模型分析，瞭解學生層次（學生知覺教師期望、能力信念、實用價值、內在價值）及班級層次（班級知覺教師期望、班級能力信念、班級實用價值、班級內在價值）重要變項之影響力，並探究能力信念在學生知覺教師期望與數理成就之間的中介效果。本研究發現，學生層次和班級層次的模型結構並不相同，在學生層次的分析中，數學和科學的能力信念對學生學業成就的直接效果最大，而在數學與科學的班級層次分析中，班級能力信念皆對班級學業成就產生相當大的直接影響。此外，學生能力信念在學生知覺教師期望與數理成就之間扮演中介角色。最後依據研究結果提供建議，以供 實務應用及未來研究之參考。 On the basis of expectancy-value theory, multilevel structural equation models and trends in mathematics and science study 2011 data were applied to investigate the effects of the student-level variables (perception of teachers' expectations, ability beliefs, utility values, and intrinsic values) and their respective class-level variables on math and science achievement, and to test the mediation effect of ability belief between students' perception of teachers' expectations and the math and science achievements of eighth-grade students in Taiwan. The study revealed the following results: (1) The student-level and class-level structures exhibited differences. (2) At the student level, students' ability belief had the strongest effect on their math and science achievement; the class level of ability belief had a positive effect on math and science achievement. (3) Ability belief had a significant mediating effect between the perception of teachers' expectations and math and science achievement. Finally, according to the results, some suggestions for practical applications and future research were introduced.